School-Based Management From the Viewpoint of the Principal’s Leadership (Study at State Vocational School 1 Bone) - Muh. Darwis; Andi Muh. Rivai; Sitti Hardiyanti Arhas; Jumadi; Bahri; Zarni Adia Purna (Technium Social Sciences Journal, 2023)
Principal leadership in school-based management (SBM) is the principal’s ability to influence and mobilize all existing resources in school management activities. This research is a qualitative descriptive study that aims to determine the leadership of the Principal in terms of School-Based Management (SBM) at SMKN 1 Bone. To achieve this goal, the researchers identified seven informants, namely school headmaster, teachers, administrative staff, students, and the community. Data collection was carried out through interviews, observation, and documentation techniques, and data analysis techniques in this study were data reduction, data presentation, and drawing conclusions. Based on the results of this study, it shows that the principal’s leadership in terms of school-based management (SBM) at SMKN 1 Bone has been carried out well based on the research focus, namely in terms of six indicators of effective principal leadership in school-based management that the principal is able to empower teachers -teachers to carry out the learning process properly, smoothly and productively, headmaster can complete assignments and work according to a predetermined time, headmaster are able to establish harmonious relationships with the community so that they can involve them actively in order to realize school and educational goals, the principal succeeded in applying leadership principles that were in accordance with the maturity level of teachers and other employees in the school, the principal was able to work with the school management team, the principal had succeeded in realizing school goals productively in accordance with predetermined provisions.